(untitled) (Damascus University Journal of agriculture sciences, 2021)
The research aims mainly to study the adoption rate of cattle breeders to fodder processing techniques and to study some of Socio-economic factors which affecting the decision of cattle breeders to adopt fodder techniques, and identify obstacles of adoption. The study was carried out in the province of Swaida during the year of 2015, the data were collected from a random sample of (119) breeders. The results of study have shown that the adoption rate of hay making technology is 12.6%, and this rate is expect to rise from 12.6% in 2014 to 45% in 2040 with annual average rate of approximately 1.25%. The results also showed that the adoption rate of treat straws with urea is 10.1% and this rate is expect to rise from 10.1% in 2013 to 70% in 2031 with annual average rate of approximately 3.33%, while there was no adoption of fodder blocks technology. The results were also shown by studying the factors influencing the adoption of hay making using the binary logical regression, there is a positive correlation between the dependent variable of hay making adoption and independent variables (the level of education, number of cows in the farm, psychological side of breeders), while a positive correlation was found between the dependent variable of treat straws with urea and independent variables (the level of education, psychological side of breeders). The results have also shown that the main determinants of adoption were lack of experience, lack of materials and equipment, small size of animal holdings, lack of land space for fodder crops.